A Quantitative Investigation of Gender-Related Variations in Coronary Artery Diameters - Imran Ellahi Soomro, Muhammad Aslam, Muhammad Amin, Aftab Ahmed, Muhammad Hassan Butt, Muhammad Hashim, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the association between gender and coronary artery diameter at the cardiac ward of a tertiary care hospital. Background: Understanding the normal structure of the coronary arteries is essential for accurately describing the amount of coronary atherosclerosis. However, studies on the true normal coronary arteries' luminal diameters are scarce. Although numerous studies have assessed the post-mortem coronary artery dimensions. A few studies have been conducted in living patients with presumed normal arteries utilizing quantitative coronary arteriography techniques Study Design: A cross-sectional study Place and Duration: This study was conducted at Peoples University of Medical and Health Sciences for women Nawabshah from December 2021 to December 2022. Methodology: The study has 121 participants. The statistical analysis was performed using SPSS version 23. We used the t-test to analyse the connection between numerical and categorical variables. A P value of 0.05 or less was considered statistically significant in every case. The patient identification number was substituted for the patient's name, angiography film number, and medical record number in the proforma, and each patient's identity was kept private. Films from coronary angiography that were deemed to be normal were gathered and examined. Results: In the present study, males were in higher proportion compared to the females with 53.72 % against 46.28%. The mean age of females was 54.9 ± 8.3 and the mean age of males was 58.7 ±9.1 Years. The mean body surface area (BSA) for males was 1.79 ±0.07 and the mean BSA for females was 1.73 ±0.02. Conclusion: Although multiple alternative explanations for the difference in coronary dimensions with gender and age have been discussed, however, in our results, coronary dimensions didn’t show a significant association with gender. There is still huge space for large-scale studies on the subject. Keywords: Coronary artery diameters, Gender Association, comparison